Cancelling self-interference in full-duplex relays without Angle-of-Arrival information - Emilio Antonio-Rodríguez; R. López-Valcarce (Int. Conf. Acoust., Speech, Signal Process. (ICASSP), 2013)
With full-duplex relays, simultaneous reception and transmission in the same frequency produce self-interference distortion and relay oscillation, hampering reception at the receiver end unless properly mitigated. Previous adaptive methods for self-interference cancellation using multiple receive antennas require knowledge of the direction of arrival of the source signal. We present a novel architecture and adaptive scheme for Amplify-and-Forward relays allowing cancellation without such knowledge. The temporal filter is updated under the property restoral paradigm in order to match the power spectrum of the retransmitted signal to that of the source signal.
Keywords: adaptive signal processing; dynacs; full duplex